Sociolinguistic Features Of Dialectal Words In English And Uzbek Languages (Eurasian Research Bulletin, 2024)
Sociolinguistics, as a field of study, focuses on the relationship between language and society, examining how language varies across different social contexts and groups. Dialects, as regionally or socially distinct varieties of a language, offer rich insights into sociolinguistic phenomena. Dialectal words reflect not only the linguistic diversity of a language but also the social, cultural, and historical contexts in which they develop. This article explores the sociolinguistic features of dialectal words in two distinct languages: English and Uzbek